Effect of Tiaojingzhixue Fang on the expression of sex hormone and endometrial tissue mRNA in perimenopausal patients with abnormal uterine bleeding - Guan, Leilei; Xue, Lili; Chu, Jingping; Xue, Jianfang; Zhang, Shuhua; Zhu, Ling (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of Tiaojingzhixue decoction on the expression of sex hormone and endometrial mRNA in perimenopausal patients with abnormal uterine bleeding. For this purpose, 84 patients with perimenopausal abnormal uterine bleeding who were treated in our hospital from January 2018 to January 2019 were divided into study group and control group, the control group was treated with mifepristone for six months, the clinical efficacy, time of symptom relief and disappearance, endometrial thickness, menstrual volume, adverse events, expression of sex hormone (ER), Progesterone receptor (PR), Lutropin (LH), Follicle-stimulating hormone (FSH), Estradiol (e2) and Vascular endothelial growth factor in endometrial tissue were compared between the two groups. The results showed that the clinical efficacy of the study group (97.61%) was significantly higher than the control group (80.95%) (P<0.05). There was no significant difference in endometrial thickness between the two groups before treatment, but after treatment for 1 month, 3 months and 6 months, endometrial thickness was thinner in the study group (P<0.05). There was no significant difference in menstrual volume between the two groups before treatment (P <0.05), but it was lower in the study group (P <0.05). The incidence of adverse reactions in the study group was 11.90% lower than in the control group (26.19%). The expression levels of ER, PR, LH, FSH and E2 were almost the same before treatment and there was no significant difference between the two groups (P>0.05), but they were lower in the study group after treatment (P<0.05). Before treatment, there was no significant difference in the level of VEGF between the two groups (P>0.05); after treatment, the level of Vegf in the study group was lower than the control group (P<0.05). After treatment, the level of Vegf in both groups was significantly higher than before treatment (P<0.05). In general, Tiaojingzhixue decoction can decrease the level of sex hormone and increase the expression of VEGF in patients with perimenopausal abnormal uterine bleeding.